Composites of phenol-formaldehyde resins filled with modified bentonites and reinforced with fiberglass mesh for application as grinding wheels - Oleksy, M.; Oliwa, R.; Szałajko, R.; Markowska, O.; Budzik, G.; Sęp, J. (Polimery, 2021)
The present study continues research on the application of bentonites modified with quaternary ammonium salts (QAS) to produce composites based on phenol-formaldehyde resin (PF). The as-prepared composites were used for impregnating fiberglass mesh of various weave and weight per unit area. The effect of the reinforcement structure (weave of fiberglass mesh) on the mechanical and structural properties of the obtained composites was investigated, especially in terms of their use as grinding wheels. Based on the obtained results, it was found that the composites with matrices containing modified aluminosilicates were characterized by greater mechanical strength and abrasion resistance, than those with non-modified matrix. On the basis of scanning electron microscopy (SEM), much better wetting of glass meshes by bentonite-modified PF compositions was observed when compared to those with unfilled phenol-formaldehyde resin.